2009
DOI: 10.1038/ni.1826
|View full text |Cite
|
Sign up to set email alerts
|

Different routes of bacterial infection induce long-lived TH1 memory cells and short-lived TH17 cells

Abstract: A sensitive peptide-major histocompatibility complex II (pMHCII) tetramer-based method was used to determine whether CD4+ memory T cells resemble the TH1 and TH-17 subsets described in vitro. Intravenous or intranasal Listeria monocytogenes infection induced pMHCII-specific CD4+ naïve T cells to proliferate and produce effector cells, about 10% of which resembled TH1 or TH-17 cells, respectively. TH1 cells were also present among the memory cells that survived three months post-infection whereas TH-17 cells di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
276
5
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 254 publications
(316 citation statements)
references
References 57 publications
29
276
5
1
Order By: Relevance
“…After 120 days, antigen‐experienced CD4 + T lymphocytes were no longer detectable in spleen or lymph nodes, while in bone marrow, a stable population had been established 59. In contrast, the group of Jenkins described the preferential location of memory CD4 + T cells in the spleen and lymph nodes until day 160 after infection, in an immune response to Listeria monocytogenes infection 126. It should be noted, however, that from day 200 onwards, in that same figure, about equal numbers of antigen‐experienced CD4 + T cells were maintained in the bone marrow, as compared to the secondary lymphoid organs.…”
Section: The Bone Marrow—hub For Circulating or Home Of Resident Memomentioning
confidence: 99%
“…After 120 days, antigen‐experienced CD4 + T lymphocytes were no longer detectable in spleen or lymph nodes, while in bone marrow, a stable population had been established 59. In contrast, the group of Jenkins described the preferential location of memory CD4 + T cells in the spleen and lymph nodes until day 160 after infection, in an immune response to Listeria monocytogenes infection 126. It should be noted, however, that from day 200 onwards, in that same figure, about equal numbers of antigen‐experienced CD4 + T cells were maintained in the bone marrow, as compared to the secondary lymphoid organs.…”
Section: The Bone Marrow—hub For Circulating or Home Of Resident Memomentioning
confidence: 99%
“…Th17 cells appear to be even less stable. Although it is now clear that in vitro generated Th17 cells and in vivo generated Th17 cells might be different in terms of developmental plasticity [154], it remains to be determined whether memory T cells that express a classic Th17 phenotype really exist [40]. Using reporter mouse/fate tracking systems, it has been shown that IL-17A or IL-17F producing T cells are reprogrammed to produce both IL-17 and IFN-c or IFN-c only in the spleen and within the CNS [155,156].…”
Section: Plasticity Of T Helper Cells In Eaementioning
confidence: 99%
“…Lymphocytes isolated from infected mice were incubated in a 96-well plate, at a concentration of 3 × 10 6 cells per well. Cells were incubated in the presence of ESAT-6 [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] or Sendai HN [421][422][423][424][425][426][427][428][429][430][431][432][433][434][435][436] peptide (5 μg/mL each) for 2 h at 37°C; Brefeldin A (50 μg/mL) was added, and the incubation was continued for an additional 4 h. Surface staining for CD4, CD8, PD-1, and KLRG1 was performed, as described previously (22), and the cells were fixed and permeabilized using a Cytofix/Cytoperm Fixation/ Permeabilization kit (BD Biosciences). For detection of intracellular IFNγ and TNFα, the cells were incubated for 30 min in Perm/Wash Buffer (BD Biosciences) with anti-IFNγ (clone XMG1.2) and anti-TNFα (clone MP6-XT22); the cells were analyzed as described above.…”
Section: Methodsmentioning
confidence: 99%